Post-stroke cognitive dysfunctions: A clinical and neuroimaging study - Andrei Yuryevich Emelin; V Yu Lobzin; S V Vorobyev; O V Dmitriev; I A Lupanov (Неврология, нейропсихиатрия, психосоматика)
Clinical, neuropsychological, and neuroimaging examinations were made in 65 patients (52 men and 13 women) aged 65.6±10.1 years who had experienced ischemic stroke. Cognitive impairments (CI) were heterogeneous; regulatory functions, attention, and counting were most significantly affected in moderate CI. In mild dementia, mainly poor attention and regulatory dysfunctions were added by clearly-cut impairments of memory, orientation, and visual-spatial function. Brain atrophy, white matter changes, and small focal gray matter damages along with focal post-stroke changes were revealed by neuroimaging in most patients. It was found that besides the volume and location of a damage focus, the signs of impaired integrated mental activity of the brain, regulatory dysfunctions in particular, should be a necessary condition for the verification of post-stroke CI.